2019
DOI: 10.1155/2019/9291216
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiome of Chinese Forest Musk Deer Examined across Gender and Age

Abstract: Animal gut microbiota begins to colonize after birth and is functionally indispensable for maintaining the health of the host. It has been reported that gender and age influence the composition of the intestinal microbiome. However, the effects of gender and age on the intestinal microorganism of forest musk deer (FMD) remain unclear. The aim of this study was to establish the relationship between the structure and composition of fecal microbiota of male and female forest musk deer with age. Here, Illumina Mis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 38 publications
4
17
0
Order By: Relevance
“…In addition, host phylogeny and divergence time could even be predicted by gut microbiota, and it brings new insights into the potential mechanisms and interrelations between host and microorganisms (Li et al., 2017 ). Although interrelations between host species and gut microbiota are important, few studies on rare and protected ruminants (Li et al., 2019 ; Naya & Karasov, 2011 ; Przybylo et al., 2019 ; Zhao et al., 2019 ). Our findings provide new insights into changes in the microbial flora and host phylogeny and provide strategies for protection.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, host phylogeny and divergence time could even be predicted by gut microbiota, and it brings new insights into the potential mechanisms and interrelations between host and microorganisms (Li et al., 2017 ). Although interrelations between host species and gut microbiota are important, few studies on rare and protected ruminants (Li et al., 2019 ; Naya & Karasov, 2011 ; Przybylo et al., 2019 ; Zhao et al., 2019 ). Our findings provide new insights into changes in the microbial flora and host phylogeny and provide strategies for protection.…”
Section: Introductionmentioning
confidence: 99%
“…2A and 2B ). Previous research in another captive center also found no significant difference in Shannon index between the sexes ( Zhao et al, 2019 ). Thus, there may be no significant differences in alpha diversity of the captive musk deer gut microbiome linked to sex.…”
Section: Resultsmentioning
confidence: 65%
“…Captivity has the potential effect on the mammal gut microbiome composition compared to that of the wild field ( Clayton et al, 2016 ). Here, the gut microbiome composition of the captive musk deer was similar across different captive centers ( Sun et al, 2020 ; Zhao et al, 2019 ). However, wild musk deer showed significant enrichment of Firmicutes, and the relative abundance of Bacteroidetes was very low ( Sun et al, 2020 ), which may be caused by different living environments (e.g., diet, and habitat).…”
Section: Resultsmentioning
confidence: 85%
“…The obtained differences in the levels of studied phyla between primiparous and multiparous ewes could also be related to the adaptation of the gastrointestinal microbiome and the changes occurring in it during pregnancy, which in turn may also be related to the age of females [ 20 , 28 ]. In the case of ruminants, changes/manipulations in the microbiome occur more easily in young animals compared to older ones, which may be related to the ability of the microbiome to adapt to both internal (physiological changes, including pregnancy) and external (under the influence of environmental factors) environments [ 29 , 30 , 31 ]. In the experiment, the ewes in the groups differed significantly in age: primiparous ewes were 12 months old while multiparous ewes were 2 years old, which means a year difference, so it can be supposed that adaptation of the microbiome to changes in hormone levels may be related to the age of the examined ewes; however, this requires further study.…”
Section: Discussionmentioning
confidence: 99%